The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1440-1711.1999.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasminogen receptor expression occurs as a degradative phase event in cellular apoptosis

Abstract: Summary Plasminogen activation (PA) is involved in a variety of extracellular proteolytic events, such as fibrinolysis, cell migration (e.g. angiogenesis, tumour cell invasion, inflammation, wound healing, bacterial invasion), ovulation, tissue remodelling and the activation of other protease classes and growth factors. These diverse roles are due to the specific localization of components of the PA system to extracellular matrices, basement membranes, fibrin and cell surfaces. We have previously reported that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…The question that arises is how plasminogen exerts its effect on corpse clearance. Previous reports have described an enhanced binding of plasminogen to the surface of apoptotic cells, suggesting that it might function as an opsonin (14)(15)(16)(17). In the current study, however, we did not observe enhanced surface binding of plasminogen to apoptotic cells.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The question that arises is how plasminogen exerts its effect on corpse clearance. Previous reports have described an enhanced binding of plasminogen to the surface of apoptotic cells, suggesting that it might function as an opsonin (14)(15)(16)(17). In the current study, however, we did not observe enhanced surface binding of plasminogen to apoptotic cells.…”
Section: Discussioncontrasting
confidence: 93%
“…Instead of acting as an opsonin, we show that plasminogen enhances efferocytosis under crucial contribution of its proteolytic activity, which is acquired after interaction with apoptotic cells. Our data are in line with studies from other groups that have attributed this activation of plasminogen to an increased expression of urokinase-type plasminogen activator, which was specifically detected on the surface of apoptotic, but not necrotic cells (15)(16)(17). Notably, plasmin(ogen)-mediated enhancement of dying cell engulfment was observed in a phase of apoptosis, in which the maximum level of PS externalization had already been reached and the integrity of the plasma membrane was still intact, suggesting that the exposure of "eat-me" signals is a prerequisite for plasmin(ogen)-dependent phagocytosis promotion.…”
Section: Discussionsupporting
confidence: 92%
“…keratin 8 as suggested by published data (39,40), whereas its nuclear accumulation might have been due to binding to chromatin components. Our results amend those of previous reports that have indicated that loss of cell viability dramatically increased plasminogen binding to the cell surface (39,41,42).…”
Section: Discussionsupporting
confidence: 88%
“…12,13 Similarly, plasmin-dependent anoikis is observed with adherent smooth muscle cells, 14,15 retinal cells, 16 and fibroblast cell lines. 17 Plasminogen binding capacity is markedly enhanced on late apoptotic/necrotic U937 monocytoid cells following treatment with cycloheximide, 18,19 suggesting a potential role for cellassociated plasminogen in regulation of apoptosis. Monocytoid cells do not depend on adherence for a survival signal.…”
Section: Introductionmentioning
confidence: 99%